Emotion-based communication: the specifics of fear and hope tactics - Juozėnaitė, Eglė (Socialiniai tyrimai, 2023)
Relevance and problem of the topic. Transmitting accurate information in the most appropriate way is an important today’s need. (Singh, Rai, et al., 2021, p. 2052). Authors Del Valle, 2021; Woodcock, 2018; Jakubanecs et al., 2019; Andrews et al., 2014; Kim et al., 2021; Gravante and Poma, 2021, states that emotional communication is often used to send a message from the sender to the recipient in a clear and compelling way, emotional communication is also used to establish an emotional connection, persuade, create associations, build loyalty, encourage desired consumer behavior. According to Dembek (2016, p. 117), emotions are separated from consumers, adjusted to become unique to the desired brand image (e.g., Coca-Cola), and then passed on to consumers in the hopes of reconciling their emotional state with marketing goals. Problems. Fear and hope tactics are quite often used as marketing and communication tools to influence an audience. It is important to understand the specifics of these communication tactics because not having enough knowledge about the reaction of recipients to these emotions, can have the opposite effect: cause adverse reactions, cause reputational crises, psychological, social, and financial losses. Properly selected communication can help companies achieve a competitive advantage in the markets, create greater added value, help shape the desired behavior of communication recipients, and predict the impact of communication on recipients. The problem analyzed in this article can be defined by the following questions: Which communication tactics, based on the emotion of fear or hope, should communication professionals use? What are the specifics of hope and fear communication tactics? What effects can they have? The objective of the research is the specifics of fear and hope tactics in communication. The object of the article is to review and analyze communication tactics based on fear and hope. Tasks: 1. To analyze the fear tactic in communication. 2. To review the tactic of hope in communication. Methods: Comparative theoretical analysis and synthesis of the literature, generalization.